2003
DOI: 10.1095/biolreprod.102.007310
|View full text |Cite
|
Sign up to set email alerts
|

Protein Inhibitor of Nitric Oxide Synthase (NOS) and the N-Methyl-d-Aspartate Receptor Are Expressed in the Rat and Mouse Penile Nerves and Colocalize with Penile Neuronal NOS1

Abstract: Nitrergic neurotransmission triggering penile erection is mediated by nitric oxide (NO) synthesized in the cavernosal nerves of the penis by penile neuronal NO synthase (PnNOS). In the central nervous system, nNOS is activated by the N-methyl-D-aspartate receptor (NMDAR) and, presumably, is inhibited by the protein inhibitor of NOS (PIN). The PnNOS and NMDAR are expressed in the penis, and PnNOS has been localized in penile nerves. Both proteins colocalize with PIN in the hypothalamus and the spinal cord invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 31 publications
0
38
0
Order By: Relevance
“…Although these nNOS modulators have been shown to be expressed in the penis [57,58] their role in the regulation of penile erection remain to be established.…”
Section: Genital Tract and Nitrergic Neurotrans-missionmentioning
confidence: 99%
“…Although these nNOS modulators have been shown to be expressed in the penis [57,58] their role in the regulation of penile erection remain to be established.…”
Section: Genital Tract and Nitrergic Neurotrans-missionmentioning
confidence: 99%
“…With the advent of molecular biological techniques, a number of researchers have demonstrated that selectively altering the expression of a targeted gene in the penile vasculature can influence the erectile response. Gene transfer of therapeutic genes has been shown to be highly efficacious in improving the diminished erectile responses in a number of experimental animal models [32,[52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71]. In general, these studies increase the amount of an endogenous vasomodulator of the erectile response or alter the sensitivity of the corporal vasculature to any given relaxatory stimulus.…”
Section: Gene Therapy For the Treatment Of Erectile Dysfunctionmentioning
confidence: 99%
“…Importantly, all three NOS enzymes (eNOS, nNOS, and iNOS) have been utilized to improve endogenous NO production in the penis [53][54][55][56][57][62][63][64][65]. Overexpression of any of the three NOS isoforms in the penis will improve a diminished erectile response in animal models of ED [53][54][55][56][57][62][63][64][65]. Both eNOS and nNOS are the most likely therapeutic gene targets to improve NO synthesis in the penis, because both isoforms are tightly regulated and produce physiological relevant levels of NO in the endothelial cells and cavernous nerves.…”
Section: Gene Therapy For the Treatment Of Erectile Dysfunctionmentioning
confidence: 99%
“…PnNOS is thought to be responsible for triggering the nitrergic mechanism responsible for cavernosal relaxation. 26,27 A similar variant, nNOSu, is present in the neuromuscular plates of skeletal muscles, 28 including the perineal muscles involved in erectile rigidity and ejaculation in rats. 29 The control of NO synthesis in the cavernosal nerve, whether due to sexual stimulation emanating centrally from the brain, or peripherally by means of the dorsal nerve spinal reflex, is assumed to be exerted through the activation of PnNOS activity.…”
Section: Synthesis Of Nomentioning
confidence: 99%
“…PIN, NMDAR subunits, and a truncated variant of the NMDAR subunit 1mRNA (NMDAR1-T) have been located in the peripheral penile nerves and pelvic ganglion. 27 The nitrergic activation of penile erection is not restricted to peripheral nerves of the corpora cavernosa but is also dependent on central nervous system control. Copulatory behavior and ejaculation are also central nervous system (CNS) regulated.…”
Section: Synthesis Of Nomentioning
confidence: 99%